2012
DOI: 10.1002/anie.201106628
|View full text |Cite
|
Sign up to set email alerts
|

A Fascinating Journey into History: Exploration of the World of Isonitriles En Route to Complex Amides

Abstract: We describe herein our recent explorations in the field of isonitrile chemistry. An array of broadly useful coupling methodologies has been developed for the formation of peptidyl and glycopeptidyl amide bonds. We further describe the application of these methods to the syntheses of complex systems, including the cyclic peptide cyclosporine A, constrained peptide systems, and heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 51 publications
0
56
0
Order By: Relevance
“…22 Our synthetic approach toward KRas(G12V) relies on the use of Fmoc-based SPPS to generate five peptidyl sequences, which are subsequently assembled via combined NCL and isonitrile-mediated activation strategies to access a biotinylated variant of KRas(G12V). 23, 24 Peptide thioesters were synthesized via Sakakibara elongation of protected peptides with pre-formed C-terminal residue thioesters following SPPS or alternatively by C-terminal hydrazide oxidation. 25,26 In a retrosynthetic fashion, taking primary advantage of the native cysteine residues within the full sequence reduces the synthetic challenge to three NCLs at assembly points Cys51, Cys80, and Cys118.…”
Section: Resultsmentioning
confidence: 99%
“…22 Our synthetic approach toward KRas(G12V) relies on the use of Fmoc-based SPPS to generate five peptidyl sequences, which are subsequently assembled via combined NCL and isonitrile-mediated activation strategies to access a biotinylated variant of KRas(G12V). 23, 24 Peptide thioesters were synthesized via Sakakibara elongation of protected peptides with pre-formed C-terminal residue thioesters following SPPS or alternatively by C-terminal hydrazide oxidation. 25,26 In a retrosynthetic fashion, taking primary advantage of the native cysteine residues within the full sequence reduces the synthetic challenge to three NCLs at assembly points Cys51, Cys80, and Cys118.…”
Section: Resultsmentioning
confidence: 99%
“…ix,x Finally, Danishefsky and coworkers recently showed that isonitriles and carboxylic acids react to form N -formyl amides, with application for the synthesis of complex peptidic structures. xi …”
Section: Introductionmentioning
confidence: 99%
“…9 The reaction of particular interest for us, drawn from our menu of new isonitrile chemistry, involves coupling of a thioacid ( 3 ) with an amine ( 5 ) in the presence of a hindered isonitrile ( 4 ). As we have shown, 10,11 this three-component reaction gives rise to an amide linkage under remarkably mild conditions .…”
mentioning
confidence: 99%